The Barry Gray Archive - Evans, François (Journal of Film Music, 2016)
The Barry Gray Archive was established in Ashford, Kent, England in 2005, to preserve and to help make available artefacts of the varied work of British film and television composer Barry Gray (1908-1984) – one of the first musicians to use electronic musical instruments in commercial, audio-visual media. This article comprises a description of the rationale behind the archive, issues faced, motivations, methods adopted for digital preservation, copyright matters engaged with and an assessment of the surprising ways in which the archive is informing British scholarship. Aspects of how an archive can be structured as an electronic hub so as to enable appropriate perpetuation are presented, together with case studies to illustrate its continuing impact to date.